(untitled) (REMUNOM, 2025)
The anime and manga series Naruto Shippuden, created by Masashi Kishimoto, is rich in elements that can be analyzed from the perspective of genetics and heredity. The narrative covers families and clans with unique abilities that are passed down from generation to generation, offering a fascinating scenario to explore scientific concepts of genetics. This study investigated the influence of genetics and heredity on the abilities of characters in the anime Naruto, making detailed comparisons with real scientific principles. The research aimed to understand how genetic and hereditary concepts are represented in the fictional narrative and how these representations can be used as effective educational tools in teaching natural sciences. The analysis identified several main clans in Naruto, such as the Uchiha, Hyuga, and Uzumaki clans, and their specific hereditary abilities. The application of genetic concepts such as alleles, dominance, and recessiveness showed how Mendelian genetics can explain the transmission of these abilities. Genetic mutations, such as the Mangekyō Sharingan and the Rinnegan, were identified, which confer extraordinary abilities to the characters. Furthermore, the research explored natural selection and evolution observed in the different clans and their abilities, highlighting how environmental and social pressures influence the propagation of advantageous traits. Comparing heredity in Naruto with real examples of genetic inheritance in humans revealed similarities and differences, providing a richer understanding of genetic principles. In conclusion, integrating Naruto into the teaching of genetics and heredity offers a unique opportunity to enrich Biology learning. Using elements of pop culture as a pedagogical resource can create a dynamic, inclusive, and engaging learning environment, promoting a deeper understanding of scientific concepts and preparing students to be critical thinkers and scientifically literate.